Determinants of Book-Tax Differences in Islamic Banking: The Moderating Role of Firm Size in the Relationship between Profitability, Deferred Tax Expense, and Tax Efficiency - Dimas Aris Setyawan; Sofie Sofie; Kathy Kathy (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study investigates the determinants of Book-Tax Differences (BTD) in Islamic banking, focusing on profitability (Return on Assets/ROA), deferred tax expense (DTE), and tax efficiency (Effective Tax Rate/ETR), with firm size as a moderating variable. The research is conducted on PT Bank Syariah Indonesia Tbk over the period 2021–2025 using quarterly financial statement data. A quantitative explanatory approach is employed using multiple regression analysis and Moderated Regression Analysis (MRA). The empirical results indicate that ROA, DTE, and ETR significantly influence Book-Tax Differences. Profitability increases managerial incentives for tax planning, resulting in higher BTD. Deferred tax expense reflects temporary differences between accounting and tax recognition, directly contributing to BTD. Meanwhile, tax efficiency (ETR) shows a negative relationship with BTD, indicating that lower effective tax rates are associated with more aggressive tax planning behavior. Furthermore, firm size significantly strengthens the relationship between the independent variables and BTD. Larger firms tend to have more complex operational structures, greater access to tax planning strategies, and higher flexibility in financial reporting, which increases the magnitude of Book-Tax Differences. This study contributes to the literature on tax accounting, earnings quality, and Islamic banking by providing empirical evidence on the interaction between financial performance, tax behavior, and organizational scale.